Social Media Marketing as a Catalyst of Digital Transformation of Business Operations - Sthapit, Arhan; Vaidya, Rashesh (Journal of Business and Social Sciences Research, 2024)
In today’s dynamic digital environment, social media marketing has become a pivotal element of digital transformation, fundamentally reshaping how businesses approach advertising, marketing strategies, and fostering customer engagement and value creation. This write-up highlights the multifaceted role of social media in enhancing brand visibility, fostering customer interactions, and driving customer value creation across economic, functional, and social dimensions. Leveraging insights from industry studies, it discusses the use of platform s to optimise operations, conduct market research, and create personalised customer experiences. Challenges such as data privacy concerns and regulatory compliance should be addressed, emphasising the need for robust data governance frameworks. The insights from the discussion underscore the importance of integrating advanced tools like AI for operational efficiency and personalised interactions. By aligning social media efforts with broader digital strategies, businesses can achieve sustainable growth in a competitive, customer-centric digital economy.